Muscle glycogen storage after prolonged exercise: Effect of the frequency of carbohydrate feedings - Burke, L. M.; Collier, G. R.; Davis, P. G.; Fricker, P. A.; Sanigorski, A. J.; Hargreaves, M. (The American Journal of Clinical Nutrition, 1996)
We reported previously that intake of carbohydrate foods with a high glycemic index (GI) produced greater glycogen storage and greater postprandial glucose and insulin responses during 24 h of postexercise recovery than did intake of low-GI carbohydrate foods. In the present study we examined the importance of the greater incremental glucose and insulin concentrations on glycogen repletion by comparing intake of large carbohydrate meals ("gorging") with a pattern of frequent, small, carbohydrate snacks ("nibbling"), which simulates the flattened glucose and insulin responses after low-GI carbohydrate meals. Eight well-trained triathletes [x +/- SEM: 25.6 +/- 1.5 y of age, weighing 70.2 +/- 1.9 kg, and with a maximal oxygen uptake (VO2max) of 4.2 +/- 0.2 L/min] undertook an exercise trial (2 h at 75% VO2max followed by four 30-s sprints) to deplete muscle glycogen on two occasions, 1 wk apart For 24 h after each trial, subjects rested and consumed the same diet composed exclusively of high-GI carbohydrate foods, providing 10 g carbohydrate/kg body mass. The "gorging" trial provided the food as four large meals of equal carbohydrate content eaten at 0, 4, 8, and 20 h of recovery, whereas in the "nibbling" trial each of the meals was divided into four snacks and fed at hourly intervals (0-11, 20-23 h).